See What's Real: Creative Brand Publicity of Netflix When Launching 'Straw Hats Unite: All Aboard the Going Merry' - Dhea Rizky Amelia; Roby Zul Fanani; Ersal Bioldy (Jobmark: Journal of Branding and Marketing Communication, 2025)
This article discusses Netflix Indonesia's creative brand publicity strategy in promoting the release of the One Piece live action film 'Straw Hats Unite: All Aboard the Going Merry.' With a qualitative descriptive approach, this study uses data collection methods through documentation and tracing of digital, media, professional, and scientific documents related to creative brand publicity and the event and momentum of the launch of the One Piece live action film. The study found that although Netflix Indonesia uses a creative brand publicity strategy with omnichannel, the launch of the Going Merry ship in PIK which is the icon of the film's narrative is the main element in this campaign. Netflix collaborated with many influencers on social media to promote the Going Merry ship and the release date of the One Piece live action film on Netflix. As a result, this campaign received a lot of organic publication from netizen content and national media.